Influence of flow and susceptibility effects on spin dephasing in lung tissue. Issue 9 (17th June 2022) - Rotkopf, Lukas T.; Kampf, Thomas; Triphan, Simon M. F.; Schlemmer, Heinz‐Peter; Ziener, Christian H.
Abstract: Purpose: Magnetic resonance imaging (MRI) of the lung can be used for diagnosis and monitoring of interstitial lung disease. Biophysical models of alveolar lung tissue are needed to understand the complex interplay of susceptibility, diffusion, and flow effects, and their influence on magnetic resonance (MR) spin dephasing. Methods: In this work, we present a method for modeling the signal decay of lung tissue by utilizing a two‐compartment model, which considers the different spin dephasing mechanisms in the alveolar vasculature and interstitial tissue. This allows calculating the magnetization dynamics and the MR lineshape, which can be measured noninvasively using clinical MR scanners. Results: The accuracy of the method was evaluated using finite element simulations and the experimentally measured lineshapes of a healthy volunteer. In this comparison, the model performs well, indicating that the relevant spin dephasing mechanisms are correctly taken into account. Conclusions: The proposed method can be used to estimate the influence of blood flow and alveolar geometry on the MR lineshape of lung tissue.